Desenvolvimento de marcadores do tipo KASP para seleção assistida do gene Rpp1 e alelos associados com resistência a Phakopsora pachyrhizi - Batti, Vinícius de Bitencourt Bez (2018)
This dissertation aimed to perform the mapping, development of SNPs and phenotypic resistance characterization of PIs 200492 (Rpp1), PI 594538A (Rpp1-b), PI 587880A (Rpp1-b) and PI 594723 (Rpp1-?). Populations evaluated were obtained through simple crosses between contrasting parents for soybean Asian rust resistance, using as a common susceptible parent for all hybridizations the line GDM15I057. Populations were phenotypically classified as resistance in discrete class, according to the observation of the reactions of immunity (IM), reddish-brown (RB), and susceptibility (TAN), later transformed into a linear scale for data analysis. Through genotyping by sequencing, of contrasting parents regarding resistance to Phakopsora pachyrhizi, genotypic markers were developed with the KASP genotyping platform. Using the GGEBiplot Software, association analysis was performed between the proposed crosses and the types of lesions observed. Using the software package R/qtl of R Software, the QTL mapping by standard interval. The genetic similarity of the populations, of resistance sources, was estimated through grouping analysis by the UPGMA method. Individuals of population PI 200492 (Rpp1) x GDM15I057 were associated with the resistance reaction RB4 and susceptibility reaction, evidencing the lower resistance to the pathogen of this source. The populations of PI 594538A (Rpp1-b) x GDM15I057 and PI 587880A (Rpp1-b) x GDM15I057, presented high levels of resistance, associating with the phenotypic reactions of immunity and RB1. The descendants of the cross between PI 594723 x GDM15I057 were associated with the reaction to MIX infection, indicating resistance only to certain P. pachyrhizi in this source. The mapping results indicate the position of PI source resistance genes 200492 (Rpp1) between GDM_KASPAR40 and S1_849484912; PI 594538 (Rpp1-b) had resistance allele mapped between S1_847603973 and S1_849484912; the mapping of the PI 587880A (Rpp1-b) found significant LOD values between markers S1_847984806 and S1_849484912; the source PI 594723 (Rpp1-?) had resistance gene mapped between the markers S1_847603973 and S1_849109823. Genotypic grouping between the resistance sources PI 594538A (Rpp1-b) and PI 587880A (Rpp1-b) showed that both have high genotypic similarity. The results observed by the cluster analysis indicate the source PI 594723 as carrier of a new Rpp1 allele.